A longitudinal study of delirium phenomenology indicates widespread neural dysfunction. Issue 2 (4th November 2013) - Leonard, Maeve; Adamis, Dimitrios; Saunders, Jean; Trzepacz, Paula; Meagher, David
Abstract: Objectives: Delirium affects all higher cortical functions supporting complex information processing consistent with widespread neural network impairment. We evaluated the relative prominence of delirium symptoms throughout episodes to assess whether impaired consciousness is selectively affecting certain brain functions at different timepoints. Methods: Twice-weekly assessments of 100 consecutive patients with DSM-IV delirium in a palliative care unit used the Delirium Rating Scale Revised-98 (DRS-R98) and Cognitive Test for Delirium (CTD). A mixed-effects model was employed to estimate changes in severity of individual symptoms over time. Results: Mean age = 7 0.2 ± 10.5 years, 51% were male, and 27 had a comorbid dementia. A total of 323 assessments (range 2–9 per case) were conducted, but up to 6 are reported herein. Frequency and severity of individual DRS-R98 symptoms was very consistent over time even though the majority of patients (80%) experienced fluctuation in symptom severity over the course of hours or minutes. Over time, DRS-R98 items for attention (88–100%), sleep–wake cycle disturbance (90–100%), and any motor disturbance (87–100%), and CTD attention and vigilance were most frequently and consistently impaired. Mixed-effects regression modeling identified only very small magnitudes of change in individual symptoms over time, including the three core domains. Significance of results: Attention is disproportionately impaired during the entire episode of delirium, consistent with thalamic dysfunction underlying both an impaired state of consciousness and well-known EEG slowing. All individual symptoms and three core domains remain relatively stable despite small fluctuations in symptom severity for a given day, which supports a consistent state of impaired higher cortical functions throughout an episode of delirium.